2008
DOI: 10.1186/1479-5876-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between NK function and response to trastuzumab in metastatic breast cancer patients

Abstract: Background: Trastuzumab is a monoclonal antibody selectively directed against Her2 and approved for the treatment of Her2 overexpressing breast cancer patients. Its proposed mechanisms of action include mediation of antibody-dependent cellular cytotoxicity (ADCC) by triggering Fc RIII on natural killer (NK) cells. This study addresses the correlation between overall NK function and trastuzumab's clinical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 31 publications
5
90
0
Order By: Relevance
“…This proposition is in line with the observation that a metastasis-free survival rate of patients can be associated with an enhanced NK cell activity (32). The clinical relevance of our data are further supported by published observations on the ADCC activity of trastuzumab in metastatic breast cancer patients (33). In this study, the in vitro ADCC activity toward Her2 overexpressing tumor cells, which was quantitatively comparable to that which was seen against Hsp70 membrane-positive tumor cells in the current study, could be correlated to the short-term antitumor responses in trastuzumab-treated breast cancer patients (33).…”
Section: Discussionsupporting
confidence: 79%
“…This proposition is in line with the observation that a metastasis-free survival rate of patients can be associated with an enhanced NK cell activity (32). The clinical relevance of our data are further supported by published observations on the ADCC activity of trastuzumab in metastatic breast cancer patients (33). In this study, the in vitro ADCC activity toward Her2 overexpressing tumor cells, which was quantitatively comparable to that which was seen against Hsp70 membrane-positive tumor cells in the current study, could be correlated to the short-term antitumor responses in trastuzumab-treated breast cancer patients (33).…”
Section: Discussionsupporting
confidence: 79%
“…Gennari and colleagues reported that the level of ADCC during trastuzumab exposure was associated with a higher efficacy of trastuzumab (16). These data were confirmed in a study done in the metastatic setting (17). All of these studies suggested that trastuzumab induced immune response that in turn mediates antitumor activity.…”
Section: Intratumoral Immune Parameters To Identify Patients Resistansupporting
confidence: 73%
“…The important mode of action is antibodydependent cellular cytotoxicity (ADCC), a reaction by which the cell-bound antibody recruits immune effector cells bearing Fcc receptors. Natural killer cells expressing Fcc receptor III (CD16) play a critical role in ADCC [19].…”
Section: Introductionmentioning
confidence: 99%